2017
DOI: 10.1186/s13570-017-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Piebald Camels

Abstract: Animal breeds are the diverse outcome of the thousands-year-long process of livestock domestication. Many of these breeds are piebald, resulting from the artificial selection by pastoralists of animals bearing a genetic condition known as leucism, and selected for their productive, behavioural, or aesthetical traits. Piebald dromedary camels have not been studied or discussed before, and their same existence is often overlooked. Based on fieldwork in Western Sahara, direct observations across Northern and East… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(60 reference statements)
1
10
0
Order By: Relevance
“…As the first exon encodes only the 5 -UTR sequence and 22 out of the 979 amino acids (MRGARGAWDLLCVLLVLLRGQT) of the signal peptide, the generated deletion can be referred to as the Kit gene knockout. Several research groups have demonstrated that the white or white-spotting phenotype represents genetic mutations in the locus near and including the Kit gene (transmembrane tyrosine kinase receptor) in various organisms, such as alpacas [58], camels [59,60], cats [61], cows [62,63], dogs [64], donkeys [65], goats [66], horses [67], mice [68][69][70], pigs [71], rabbits [72], rats [73], yaks [74], humans [75,76], and even zebrafish [77]. The molecular mechanism behind this phenotype is linked to melanocyte migration and survival maintained by tyrosine-protein kinase KIT receptor.…”
Section: Large Unexpected Deletion In the Target Regionmentioning
confidence: 99%
“…As the first exon encodes only the 5 -UTR sequence and 22 out of the 979 amino acids (MRGARGAWDLLCVLLVLLRGQT) of the signal peptide, the generated deletion can be referred to as the Kit gene knockout. Several research groups have demonstrated that the white or white-spotting phenotype represents genetic mutations in the locus near and including the Kit gene (transmembrane tyrosine kinase receptor) in various organisms, such as alpacas [58], camels [59,60], cats [61], cows [62,63], dogs [64], donkeys [65], goats [66], horses [67], mice [68][69][70], pigs [71], rabbits [72], rats [73], yaks [74], humans [75,76], and even zebrafish [77]. The molecular mechanism behind this phenotype is linked to melanocyte migration and survival maintained by tyrosine-protein kinase KIT receptor.…”
Section: Large Unexpected Deletion In the Target Regionmentioning
confidence: 99%
“…For example, sequencing the KIT (Tyrosine kinase receptor) gene revealed the variants associated with the white-spotting phenotype of piebald (painted) camels (Holl et al, 2017; Volpato et al, 2017). The candidacy of this gene was established based on findings in other animals.…”
Section: Introductionmentioning
confidence: 99%
“…The extension and distribution of white spots conditions the degree of deafness and visual deficit. Both impairments have been reported to be associated to certain predominant behavioral patterns [41]. This has been specifically dealt with in other species such as cows.…”
Section: Coat and Eye Color Genetics May Reflect Camel Temperamentmentioning
confidence: 97%
“…Variables in the first block were chosen because of the implications of overall body condition [39] and body size on the determination of camel intraherd hierarchy [24,40]. The second block was considered because of the implication of phaneroptics with behavioral traits [41]. The third and fourth blocks were included as well, as the variables measured therein have often been reported to be either determinants or confounding in the determination of camel hierarchy status in camels and other species [24,[42][43][44]…”
Section: Ordinal Logistic Regressionmentioning
confidence: 99%
See 1 more Smart Citation